2020
DOI: 10.1002/jssc.202001007
|View full text |Cite
|
Sign up to set email alerts
|

Stability indicating RP‐HPLC method for determination of dimethyl fumarate in presence of its main degradation products: Application to degradation kinetics

Abstract: A stability‐indicating reverse phase‐high‐perfromance liquid chromatography method for the quantitative determination of dimethyl fumarate in presence of its main degradation products was developed. The chromatographic conditions were optimized using two‐level full factorial design, chromatographic analysis was performed using Inertsil® column (250 × 4.6 mm, 5 μm) maintained at 25°C. Mobile phase was a mixture of water (pH 2.6 adjusted with phosphoric acid) and methanol (40:60, v/v) at a flow rate 1.0 mL/min, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The chemical kinetics of the reaction are concerned with the determination of chemical reaction rates as well as the factors influencing these rates [18]. Chemical degradation kinetics are necessary for pre‐formulation studies, defining the optimal storage conditions, forecasting the drug's shelf life and the selection of appropriate drug delivery vehicles [19].…”
Section: Resultsmentioning
confidence: 99%
“…The chemical kinetics of the reaction are concerned with the determination of chemical reaction rates as well as the factors influencing these rates [18]. Chemical degradation kinetics are necessary for pre‐formulation studies, defining the optimal storage conditions, forecasting the drug's shelf life and the selection of appropriate drug delivery vehicles [19].…”
Section: Resultsmentioning
confidence: 99%
“…Main effect plots (Figure S4) revealed that increasing SDS, Na 2 HPO 4 , and %butanol caused a decrease in run time but also efficiency (N) decreased and the tailing factor increased. Interaction plots (Figure S5) indicated that there were multiple interactions between studied factors and responses optimized, thus factorial design gave us more reliable conditions rather than one factor at a time optimization [41,42].…”
Section: Hplc Methods Development and Optimizationmentioning
confidence: 99%
“…ICH guidelines [18] require developing stability indicating assay methods (SIAM) for active ingredients to elucidate drug inherent stability with time [19]; also, the linear regression analysis of degradation with time is required [20,21]. Degradation kinetics and pH profiling is required [22] for determining optimum storage conditions and predicting shelf life of drug [23,24].…”
Section: Introductionmentioning
confidence: 99%